1976
DOI: 10.1063/1.322705
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous ion combination coefficients in sulphur hexafluoride

Abstract: The homogeneous ion neutralization coefficient in SF6 has values of 1.0±0.1, 1.2±0.1, 1.1±0.1, and 1.2±0.7×10−6 cm3 s−6 respectively at 150, 356, 550, and 603 Torr for ions created by pulses of x rays. The results are compared with calculated three-body neutralization coefficients for monomer and dimer ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

1976
1976
2006
2006

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 10 publications
1
0
0
Order By: Relevance
“…The range of pressures in our experiments corresponds to that investigated by Wilson et al (1976) and to the plateau region observed by Schmidt and coworkers intermediate between the high-and low-pressure regimes. Measurements at 20 Torr yielded recombination rates which were approximately a factor of five lower than those measured at the higher pressures, also in agreement with the results of Schmidt and COworkers.…”
Section: Resultssupporting
confidence: 83%
“…The range of pressures in our experiments corresponds to that investigated by Wilson et al (1976) and to the plateau region observed by Schmidt and coworkers intermediate between the high-and low-pressure regimes. Measurements at 20 Torr yielded recombination rates which were approximately a factor of five lower than those measured at the higher pressures, also in agreement with the results of Schmidt and COworkers.…”
Section: Resultssupporting
confidence: 83%
“…Rate coefficients for the combination of positive and negative ions in SF6 were measured (93). Recombination rate coefficients involving water, air, C02, and O2 were determined respectively by (46,175,222).…”
Section: Atoms and Moleculesmentioning
confidence: 99%